Antioxidant activity of pleurotus species and antidiabetic activity of pleurotus citrinopileatus (singer) / Rushitha Sadasevevam - Sadasevevam, Rushitha (2011)
The genus Pleurotus comprises some of the most popular edible mushrooms due to their favourable organoleptic and medicinal properties, vigorous growth and undemanding cultivation conditions. Pleurotus species contain a variety of secondary metabolites including various phenolic compounds which have been said to act as excellent antioxidants and possess antidiabetic activity. The antioxidant activity of mycelial extract of nine Pleurotus species and antidiabetic activity for Pleurotus citrinopileatus was investigated. The total phenolic content in mycelial extract of nine Pleurotus species was assayed by Folin-Ciocalteau’s method while antioxidant activity was determined by two different assays namely scavenging effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and ferric reducing antioxidant power (FRAP) assay. Mycelial extract of P. flabellatus exhibited the highest total phenolic content with 233.53±3.60 mg of GAEs/g of extract. Mycelial extract of P. sajor caju exhibited highest FRAP value with 28.20 ±0.19 μmol of FeSO4.7H2O equivalents/g of extract respectively. Mycelial extract of P. cystidiosus showed the most potent DPPH radical scavenging activity of 0.599 mg/ml at which 50% of DPPH radical were scavenged. The antidiabetic property of P. citrinopileatus was investigated by analysis of fasting blood glucose level, fasting body weight, fasting insulin and catalase level throughout the 45 days of treatment, with a long term view towards the possible use of this mushroom in the treatment of diabetes. The results showed that fasting blood sugar level of STZ induced diabetic rats fed on Pleurotus citrinopileatus dropped by day 30 and returned back to normal when compared to normal rats. Diabetic rats treated with mycelial extract of P. citrinopileatus showed an increase in body weight after 30 days of treatment compared to diabetic rats treated with water. iii By the end of 45 days, no significant difference was observed in fasting insulin level between normal group and diabetic group of rats treated with high dose of mycelial extract. Fasting catalase level marks no significant difference between normal rats and diabetic rats treated with mycelial extract of P. citrinopileatus. Histological section of the kidney of STZ induced diabetes rats treated with 1000 mg/kg of mycelial extract showed a very mild congestion of glomeruli and interstitium stroma of cortex. Hence, the consumption of selected Pleurotus species grown in tropical conditions may have health promoting benefits as it is taken in appropriate dose as food supplement in daily life.